Utilization of Treated Wastewater from the Ready-Mix Concrete Industry for Road Spraying: Pemanfaatan Air Limbah Terolah dari Industri Beton Ready Mix untuk Penyiraman Jalan - Rosyadah, Sabrina Haifa; Putro, Raden Kokoh Haryo; Arohmah, Nicken Elok (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The ready-mix concrete industry plays a crucial role in supplying concrete for various construction purposes. During its production and operational processes, this industry generates wastewater from laboratory activities, mixer van washing, and truck mixer cleaning. The generated wastewater is treated and planned to be reused for road spraying within the industrial area. This paper aims to analyze the characteristics of the generated wastewater and its potential impact on roads, and evaluate the efficiency of its reuse. The total volume of treated wastewater produced is 11.88 m³/day, containing parameters such as pH, TSS, Cl⁻, and SO₄²⁻. Based on the water quality measurements, the treated wastewater meets the quality standards set by the Ministry of Environment and Forestry for pH and TSS, and by Government Regulation No. 22 of 2021 for chloride and sulfate. Therefore, the wastewater is considered suitable for road spraying. The efficiency of using treated wastewater for this purpose reaches 43% during the dry season and 86% during the rainy season.